Spinal and pelvic kinematics during prolonged rowing on an ergometer vs. indoor tank rowing - Trompeter, K.; Weerts, J.; Fett, D.; Firouzabadi, A.; Heinrich, K.; Schmidt, H.; Brüggemann, G.-P.; Platen, P. (The Journal of Strength and Conditioning Research, 2021)
This investigation aimed to compare spinopelvic kinematics during rowing on an ergometer vs. in a rowing tank and to evaluate changes with progressing fatigue. Spinal and pelvic kinematics of 8 competitive scull rowers (19.0 ± 2.1 years, 179.9 ± 7.6 cm, and 74.8 ± 8.1 kg) were collected during 1 hour of rowing on an ergometer and in a rowing tank using a routine training protocol. Kinematics of the upper thoracic spine, lower thoracic spine, lumbar spine, and pelvis were determined using an infrared camera system (Vicon, Oxford, United Kingdom). There was a greater lumbar range of motion (ROM) and less posterior pelvic tilt at the catch during rowing on the ergometer compared with in the rowing tank (p = 0.001-0.048), but no differences in pelvic ROM. In the rowing tank, the pelvic ROM increased over time (p = 0.002) and the ROM of the lower thoracic spine decreased (p = 0.002). In addition, there was an extended drive phase (when the rower applies pressure to the oar levering the boat forward) and an abbreviated recovery phase (setting up the rower's body for the next stroke) in the rowing tank (p = 0.032). Different rowing training methods lead to differences in spinopelvic kinematics, which may lead to substantially different spinal loading situations. Greater pelvic rotation and lesser lumbar ROM are considered ideal; therefore, the present results indicate that rowing in the rowing tank might facilitate the maintenance of this targeted spinopelvic posture, which might help protect the lower back. Rowers, coaches, and researchers should consider the differences between rowing training methods, especially when giving training recommendations.